Relationship of Education of Papua Youth Original Students on Nationalism in Medan City - Weya, Ince; Nasution, Zulkifli; Revida, Erika (TALENTA Publisher, Universitas Sumatera Utara, 2021)
This research was conducted on young people from Papua who studied in Medan at 3 state universities, namely: University of North Sumatra, Medan State University, and Medan State Polytechnic. a total population of 147 and taken as a sample of 35% (50) of the total population taken at random (simple random sampling) research members in this population are considered homogeneous. This research was conducted in December 2019 - February 2020. The results showed the value of Product Moment correlation between the education of young Papuan students and nationalism in the city of Medan. Product Moment correlation value is 0.509 greater than 0.5 which indicates the education of young Papuan students and nationalism is very closely correlated. Given the Sig (2-tailed) value is 0,000 <significance level of 0.05, it is concluded that the education of young Papuan students and nationalism has a significant correlation. In other words, the better a person's education is, the higher the person's nationalism level.